Operational Business Planning: Bunnies After School Program and Daycare - Chartini Chartini; Tantri yanuar rahmat syah; Samerdanta Pusaka; Darmansah Darmansah (Journal of Multidisciplinary Academic, 2019)
The purpose of Bunnies After School Program and Daycare business planning is a child care agency with an age range about 0 months to 12 years that can help the role of parents in caring and nurturing children by providing the best service to meet customer demand for customer satisfaction. Bunnies after School Program and Daycare operational planning stages include LFR, ARC, Curriculum and Program. Otherwise, it uses Lean Process, Service Blue Print, and Integrated Marketing Communication. Strategic location is needed to support this daycare business, the location plan is at the residential complex of Scientia Garden Serpong Street, South Tangerang City, Province Banten. This study method uses a SWOT matrix to see opportunities and competition in the daycare business. The daycare Bunnies business is a service to optimally explore children's intellectual, talent and intelligence for parents who are busy at work so they can work in peace.